Pengembangan Plugin “Edupro” Berbasis Project Based Learning Di Moodle untuk Meningkatkan Kompetensi Pemrograman Berorientasi Objek (Studi Kasus Siswa Kelas XI RPL SMKN 1 Surabaya) - Rahman, Ghufran Fathur; Ekohariadi, Ekohariadi (IT-Edu : Jurnal Information Technology and Education, 2025)
This study aims to design, development, and evaluate the effectiveness of the "Edupro" website-based plugin on the Moodle platform in enhancing the object-oriented programming competency of Software Engineering (RPL) students at SMK Negeri 1 Surabaya. The plugin was developed using a Project-Based Learning (PjBL) approach and the ADDIE development model, designed to support active learning and the development of students' cognitive and psychomotor skills. Expert evaluations indicated excellent validity levels for the media (98%), lesson plans (82%), materials (91%), and evaluation questions (92%), suggesting that the media is highly suitable for learning. The results of the paired sample t-test evaluation showed a significant improvement in students' cognitive and psychomotor understanding, with average posttest scores higher than pretest scores (77.63 > 54.3 for cognitive and 78.88 > 55.83 for psychomotor). The hypothesis testing using a paired sample t-test with a Sig.(2-tailed) value of 0.000 (<0.05) confirms that the use of the "Edupro" website-based plugin can improve object-oriented programming learning outcomes for XI grade Software Engineering (RPL) students at SMK Negeri 1 Surabaya.